PENINGKATAN KUALITAS PENDIDIKAN MELALUI KUALIFIKASI DAN KOMPETENSI AKADEMIK - Umi Salamah (STAI Ma'had Aly Al-Hikam Malang, 2019)
This study aims to determine the improvement of the quality of education through academic qualifications and competencies. The research method used is a qualitative descriptive method. Data collection techniques carried out in this study used observation, interviews, and documentation. The subjects in this study were students of STAI Ma'had Aly Al-Hikam Malang Madrasah Ibtidaiyah Teacher Education (2017/2018). The results of this study obtained data that the previous academic qualifications were not appropriate / not linear with basic education, improving the quality of education through academic qualifications and competencies had a positive effect on education in MI.